Titanium oxide / zinc oxide co-doped polyetherimide antistatic film as well as preparation method and application thereof
ZnO and TiO2 are circulated on the PEI film by gas-phase permeation method, and the doping ratio is adjusted, and the titanium oxide/zinc oxide co-doped polyetherimide antistatic film is prepared, which solves the problems of poor antistatic performance and mechanical properties in the prior art, and achieves efficient improvement of antistatic performance and material stability maintenance.
Patent Information
- Application Number
- CN202411993816.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, the antistatic properties of modified polyetherimides have poor durability, affect the mechanical properties of polyetherimides, low doping efficiency and complex post-treatment.
ZnO and TiO2 are circulated on the PEI film by gas-phase permeation method, and the ratio of the total permeation cycles between TiO2 and ZnO is regulated, so as to achieve the preparation of titanium oxide/zinc oxide co-doped polyetherimide antistatic film.
It significantly improves the antistatic properties, maintains the mechanical properties and stability of the material, and has a simple process and controllable doping process, making it suitable for industrial applications.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of development of organic photoelectric materials, and relates to a titanium oxide / zinc oxide co-doped polyetherimide antistatic film and a preparation method and application thereof. Background Art
[0002] In many fields such as electronic equipment, semiconductor manufacturing, and medical equipment, the problem of static electricity has always been a key problem that needs to be solved urgently. Traditional polymer materials are prone to static electricity accumulation due to friction, contact separation, and other factors during use. When static electricity accumulates to a certain extent, electrostatic discharge will occur, which may cause damage to precision electronic components, such as breakdown and malfunction of electronic components, seriously affecting the reliability and service life of the equipment. Polyetherimide (PEI) is a high-performance thermoplastic material that is widely used in various industrial fields due to its excellent mechanical strength, chemical resistance, and high temperature resistance. However, since PEI itself has a high volume resistivity, it is easy to accumulate static charge during use, which limits its application in certain sensitive environments. Therefore, it is very important to eliminate the static electricity hazards of high-performance PEI materials. At present, the methods to improve the antistatic properties of PEI mainly include surface coating of antistatic agents, adding conductive fillers, and blending conductive polymers. However, these methods have some problems: the antistatic agent coated on the surface has poor durability and is easy to fall off; the addition of conductive fillers may affect the mechanical properties and stability of the material; the blended conductive polymer is mainly achieved by liquid phase doping, which has the disadvantages of uneven distribution, low doping efficiency, complex post-processing and potential environmental risks, which affect its application in high-performance materials. Therefore, it is necessary to develop a method that can effectively improve the antistatic performance while maintaining other excellent properties. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a titanium oxide / zinc oxide co-doped polyetherimide antistatic film and a preparation method and application thereof, thereby solving the technical problems that the modified polyetherimide obtained in the prior art has poor antistatic durability, affects the mechanical properties of the polyetherimide, has low doping efficiency and complex post-processing.
[0004] The present invention is achieved through the following technical solutions: A method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film comprises the following steps: The titanium oxide / zinc oxide co-doped polyetherimide antistatic film is prepared by sequentially and cyclically permeating ZnO and TiO2 on the PEI film several times by using a vapor phase permeation method; Among them, the ratio of the total number of cyclic penetrations of TiO2 to the total number of cyclic penetrations of ZnO is (1~4):40.
[0005] Preferably, the total number of infiltration cycles of ZnO is 200 times, and the total number of infiltration cycles of TiO2 is 5 to 20 times.
[0006] Preferably, the ZnO and TiO2 are sequentially and cyclically infiltrated on the PEI film several times by using a vapor phase infiltration method, specifically: First, 50 ZnO infiltration cycles were performed, and then TiO2 infiltration cycles and ZnO infiltration cycles were performed alternately for a total of 5 times. In each alternating infiltration, TiO2 infiltration cycles were performed 1 to 4 times, and ZnO infiltration cycles were performed 30 times.
[0007] Preferably, ZnO and TiO2 are sequentially cyclically infiltrated on the PEI film several times by vapor phase infiltration method, specifically: 50 ZnO infiltration cycles are first performed, and then TiO2 infiltration cycles and ZnO infiltration cycles are alternately performed for a total of 5 times, and in each alternating infiltration, TiO2 infiltration cycle is performed once and ZnO infiltration cycle is performed 30 times.
[0008] Preferably, a ZnO cycle permeation process is as follows: a diethyl zinc vapor pulse of 0.02-0.05s is introduced into the gas phase permeation chamber, and is maintained in the gas phase permeation chamber for 70-75s, and then N2 is purged for 70-75s; then a water vapor pulse of 0.02-0.05s is introduced into the gas phase permeation chamber, and is maintained in the gas phase permeation chamber for 70-75s, and finally N2 is purged for 70-75s, to complete a ZnO cycle permeation; One of the TiO2 cyclic infiltration processes is as follows: a TiCl4 vapor pulse of 0.02 to 0.05 s is introduced into the gas phase infiltration chamber, and maintained in the gas phase infiltration chamber for 70 to 75 s, and then N2 is purged for 70 to 75 s; then a water vapor pulse of 0.02 to 0.05 s is introduced into the gas phase infiltration chamber, and maintained in the gas phase infiltration chamber for 70 to 75 s, and finally N2 is purged for 70 to 75 s to complete a TiO2 cyclic infiltration.
[0009] Preferably, a ZnO cycle permeation process is as follows: a pulse of diethyl zinc vapor is introduced into the gas phase permeation chamber for 0.05 s, and maintained in the gas phase permeation chamber for 75 s, and then N2 is purged for 75 s; then a pulse of water vapor is introduced into the gas phase permeation chamber for 0.02 s, and maintained in the gas phase permeation chamber for 75 s, and finally N2 is purged for 75 s, to complete a ZnO cycle permeation; One of the TiO2 cyclic infiltration processes is as follows: a TiCl4 vapor pulse of 0.05s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 75s, and then N2 is purged for 75s; then a water vapor pulse of 0.02s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 75s, and finally N2 is purged for 75s to complete a TiO2 cyclic infiltration.
[0010] Preferably, during the ZnO cyclic infiltration process and the TiO2 cyclic infiltration process, the temperature of the gas phase infiltration chamber is maintained at 90-95°C and the pressure is maintained at 10000-12000Pa.
[0011] Preferably, before cyclically permeating ZnO and TiO2 on the PEI film in sequence by vapor permeation method, the PEI film is placed in a vapor permeation chamber, and the pressure in the vapor permeation chamber is controlled to be 40~75Pa, and then an inert gas is introduced at a flow rate of 40~75sccm for 10 minutes.
[0012] A titanium oxide / zinc oxide co-doped polyetherimide antistatic film is prepared by the above method; the conductivity of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film is (1.1~3.6)×10 -5 S / cm, the friction voltage is -0.25~0.8V, and the stress is 10.2~10.6Mpa.
[0013] The above-mentioned titanium oxide / zinc oxide co-doped polyetherimide antistatic film is used in antistatic equipment.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film. The method utilizes a multi-precursor vapor phase infiltration technology based on atomic layer deposition (ALD) to infiltrate vapor phase precursor molecules into a polymer matrix, react with functional groups in the polymer, and achieve in-situ doping modification of the PEI film. The metal organic precursor infiltrated by the method can react chemically on the subsurface and internal area of the substrate, thereby producing a new hybrid material. The metal precursor molecules diethyl zinc (DEZ) and TiCl4 form ZnO and TiO2 through vapor phase infiltration (VPI), thereby achieving co-doping of the PEI film, and the antistatic performance of the PEI film is regulated by adjusting the ratio of the total number of infiltration cycles of TiO2 and ZnO. The process not only does not introduce solvent molecules, successfully eliminates the influence of the liquid phase environment on the morphology and structure of the polymer film, but also can achieve precise regulation of the doping amount of various precursor molecules inside the polymer matrix. The C=O double bond in PEI combines with the Zn atom in ZnO to form a chemical bond with high stability, which greatly improves the bonding strength between the dopant and the matrix, and can maintain the stability of the optical and mechanical properties of the film material while maintaining the improvement of the electrical properties of the film. In addition, the Ti atom combines with the Zn atom, and the Ti atom has four bonds, which effectively improves the transmission path of the electrons and improves the antistatic properties of the material. Therefore, the preparation method of the present invention is simple, the doping process is controllable, the structure and properties of the modified polymer film are stable, and the electrical conductivity of the material is greatly improved, so it has a very high industrial application prospect and use benefit.
[0015] Furthermore, the total number of permeation cycles of ZnO is 200 times, and the total number of permeation cycles of TiO2 is 5 to 20 times. ZnO is the main matrix for improving the electrical properties of the material, and the role of TiO2 is, on the one hand, to increase the concentration of material carriers, and on the other hand, the introduction of Ti can provide more branched pathways for charge discharge.
[0016] Furthermore, the vapor phase infiltration method was used to cyclically infiltrate ZnO and TiO2 on the PEI film for several times. Specifically, 50 ZnO infiltration cycles were performed first, and then TiO2 infiltration cycles and ZnO infiltration cycles were performed alternately for a total of 5 times. In each alternating infiltration, TiO2 infiltration cycles were performed 1 to 4 times, and ZnO infiltration cycles were performed 30 times, so that TiO2 was evenly distributed in the ZnO layer.
[0017] Furthermore, the vapor phase infiltration method was used to cyclically infiltrate ZnO and TiO2 on the PEI film for several times, specifically: 50 ZnO infiltration cycles were performed first, and then TiO2 infiltration cycles and ZnO infiltration cycles were performed alternately for a total of 5 times. In each alternating infiltration, TiO2 infiltration cycle was performed once and ZnO infiltration cycle was performed 30 times. ZnO infiltration was performed first and then TiO2 infiltration was performed, which can make Ti atoms combine with ZnO chains and provide additional branching sites.
[0018] Further, a ZnO cyclic infiltration process is as follows: a diethyl zinc vapor pulse of 0.02 to 0.05 s enters the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 70 to 75 s, and then N2 is purged for 70 to 75 s; then a water vapor pulse of 0.02 to 0.05 s enters the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 70-75 s, and finally N2 is purged for 70 to 75 s, completing a ZnO cyclic infiltration; a TiO2 cyclic infiltration process is as follows: a TiCl4 vapor pulse of 0.02 to 0.05 s enters the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 70-75 s, and finally N2 is purged for 70 to 75 s, completing a ZnO cyclic infiltration. Enter the gas permeation chamber and keep it in the gas permeation chamber for 70~75s, then purge with N2 for 70~75s; then pulse water vapor into the gas permeation chamber for 0.02~0.05s and keep it in the gas permeation chamber for 70~75s, finally purge with N2 for 70~75s to complete a TiO2 cycle permeation. The long-term retention of the precursor gas here can promote the reaction gas to enter the polymer matrix through the mesopores and micropores. Each long-term nitrogen purge can timely remove the unreacted precursor molecules and reaction by-products in the reaction chamber.
[0019] Furthermore, during the ZnO cyclic infiltration process and the TiO2 cyclic infiltration process, the temperature of the gas phase infiltration chamber is maintained at 90~95°C and the pressure is maintained at 10000~12000Pa, so that the consistency of the infiltration temperature can be ensured during the reaction process. The reaction temperature of 90°C can provide a driving force for the combination of the precursor and the substrate.
[0020] Furthermore, before cyclically infiltrating ZnO and TiO2 on the PEI film in sequence by vapor infiltration, the PEI film was placed in a vapor infiltration chamber, and the pressure in the vapor infiltration chamber was controlled to be 40~75Pa. Then, an inert gas was introduced at a flow rate of 40~75sccm for 10 minutes, which can effectively remove moisture and residual organic solvents on the sample surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 The SEM images of the PEI film before and after multiple gas phase permeation in Example 1 of the present invention are shown in Figure (a). The PEI / ZnO (200 cycles) film is shown in Figure (b). The PEI / TZO (1:40) film is shown in Figure (b). Figure 2 XPS images of PEI / ZnO (200 cycles) and PEI / TZO (x: 40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention; Figure 3 The electrical performance images of PEI / ZnO (200 cycles) and PEI / TZO (x: 40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention are shown; Figure 4 The graphs are the changes in the conductivity of PEI / ZnO (200 cycles) and PEI / TZO (x: 40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention; Figure 5 The tribovoltage diagrams of PEI / ZnO (200 cycles) and PEI / TZO (x: 40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention; Figure 6 The stress-strain curves of PEI / ZnO (200 cycles) and PEI / TZO (x: 40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention are shown. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0025] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0026] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0027] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0028] The present invention provides a method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film, comprising adopting a multiple vapor phase infiltration technique, using diethyl zinc (DEZ), TiCl4 and H2O as precursors, and in-situ doping and modifying a PEI film using TiO2 and ZnO through vapor phase infiltration to prepare a polyetherimide antistatic film based on in-situ doping modification; Among them, the preparation of PEI antistatic film is achieved by controlling the total number of ZnO cycles to be the same and changing the ratio of TiO2 and ZnO in the gas phase infiltration cycle.
[0029] Preferably, the specific operations of the above-mentioned gas phase permeation cycle include: 1) Place the PEI initial film into the reaction chamber of the vapor phase infiltration (VPI) device, control the pressure of the reaction chamber to 40-75 Pa, and then introduce inert gas at a flow rate of 40-75 sccm for 10 min; 2) ZnO infiltration process, a ZnO cyclic infiltration process is as follows: diethyl zinc vapor pulse 0.02-0.05s into the gas phase infiltration chamber, and kept in the gas phase infiltration chamber for 70-75s, and then N2 purged for 70-75s; then water vapor pulse 0.02-0.05s into the gas phase infiltration chamber, and kept in the gas phase infiltration chamber for 70-75s, and finally purged with N2 for 70-75s, to complete a ZnO cyclic infiltration; Preferably, a ZnO cycle permeation process is as follows: a pulse of diethyl zinc vapor is introduced into the gas phase permeation chamber for 0.05 s, and maintained in the gas phase permeation chamber for 75 s, and then N2 is purged for 75 s; then a pulse of water vapor is introduced into the gas phase permeation chamber for 0.02 s, and maintained in the gas phase permeation chamber for 75 s, and finally N2 is purged for 75 s, to complete a ZnO cycle permeation; 3) TiO2 infiltration process, a TiO2 cyclic infiltration process is as follows: a TiCl4 vapor pulse of 0.02-0.05s is introduced into the gas phase infiltration chamber, and maintained in the gas phase infiltration chamber for 70-75s, and then N2 is purged for 70-75s; then a water vapor pulse of 0.02-0.05s is introduced into the gas phase infiltration chamber, and maintained in the gas phase infiltration chamber for 70-75s, and finally N2 is purged for 70-75s to complete a TiO2 cyclic infiltration.
[0030] Preferably, a TiO2 cyclic infiltration process is as follows: a TiCl4 vapor pulse of 0.05s is introduced into the gas phase permeation chamber, and maintained in the gas phase permeation chamber for 75s, and then N2 is purged for 75s; then a water vapor pulse of 0.02s is introduced into the gas phase permeation chamber, and maintained in the gas phase permeation chamber for 75s, and finally N2 is purged for 75s to complete a TiO2 cyclic infiltration.
[0031] In addition, x is used to represent the number of infiltration cycles of TiO2, that is, the total number of infiltration cycles. The ratio of the total number of cyclic infiltration cycles of TiO2 to the total number of infiltration cycles of ZnO is (1~4):40, and the preferred ratio is TiO2:ZnO=1:40, 2:40, 3:40 and 4:40, wherein the total number of cycles of ZnO is 200 times. First, infiltrate ZnO, repeat step 2) 50 times, introduce ZnO phase into PEI to make it react initially with the inside of the matrix. Then, perform multiple doping operations, first infiltrate TiO2, repeat step 3) x times, then infiltrate ZnO, repeat step 2) 30 times, repeat the multiple doping operations 5 times, and obtain a PEI / TZO (x:40) film.
[0032] During the permeation cycle, the temperature in the reaction chamber is 90-95° C. and the pressure is 10000-12000 Pa.
[0033] In addition, the present invention discloses a titanium oxide / zinc oxide co-doped polyetherimide antistatic film, which is prepared by the above method. The conductivity of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film is (1.1~3.6)×10 - 5 S / cm, the friction voltage is -0.25~0.8V, and the stress is 10.2~10.6Mpa.
[0034] The present invention discloses a method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film, which adopts a simple and efficient method, and utilizes a multi-precursor vapor phase infiltration technology based on atomic layer deposition (ALD) to infiltrate vapor phase precursor molecules into a polymer matrix, react with functional groups in the polymer, and achieve in-situ doping modification of the PEI film. This method is repeated (circulated) in the same way as ALD, and the infiltrated metal organic precursor can react chemically on the subsurface and internal area of the substrate, thereby producing a new hybrid material. ZnO and TiO2 formed by the metal precursor molecules DEZ and TiCl4 through the VPI process are used to dope and modify the PEI film, and the antistatic properties of the PEI film are regulated by adjusting the ratio of the formed TiO2:ZnO (TZO). The VPI process adopted not only does not introduce solvent molecules, successfully eliminates the influence of the liquid phase environment on the morphology and structure of the polymer film, but also can achieve precise regulation of the doping amount of various precursor molecules inside the polymer matrix. The C=O double bond in PEI combines with the Zn atom in ZnO to form a chemical bond with high stability, which greatly improves the bonding strength between the dopant and the matrix, and can maintain the stability of the optical and mechanical properties of the film material while maintaining the improvement of the electrical properties of the film. Therefore, the preparation method disclosed in the present invention has the advantages of simple operation, controllable doping process, and stable structure and properties of the polymer film after modification. After modification, the conductivity of the material is greatly improved, and thus it has a very high industrial application prospect and use benefit. In the preparation method of the present invention, through the cyclic infiltration operation of infiltration-purge, and the exposure and purge time are clarified, under the premise of ensuring that the precursor and the polymer film are fully reacted, the excess precursor is avoided from being deposited on the surface of the polymer film, which is not conducive to the reaction degree of in-situ doping modification, and at the same time, it is conducive to the conduction of the reaction degree in the subsequent gas phase infiltration cycle.
[0035] In addition, the present invention prepares the PEI film by using a solution casting method, and specifically provides a mixing ratio of PEI and a good solvent, so that the PEI film has a certain thickness, which is beneficial to the penetration and reaction combination of precursor molecules and improves the in-situ doping modification effect of the film material.
[0036] The present invention also discloses a PEI antistatic film based on multiple precursor doping modification obtained by the above-mentioned preparation method, which is a new type of organic-inorganic hybrid material. Compared with the initial film material, the introduction of TiO2 in the modified film material increases the concentration of carriers in the film, and at the same time changes the binding mode of the original functional groups in the matrix, causing the electron cloud state to change, thereby improving the conductivity to a certain extent. Different PEI films are obtained by adjusting the ratio of TiO2 and ZnO during the gas phase infiltration cycle, and their conductivity is improved to varying degrees, and the mechanical and optical properties of the modified film material are stable. Therefore, the PEI film based on multiple precursor doping modification disclosed in the present invention can be put into practical applications as an antistatic film material and has very considerable economic benefits. The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0038] In the specific embodiments of the present invention, a PEI initial film is selected as the substrate material, and a vapor infiltration technique is adopted. TZO and H2O are used as precursors, and the PEI initial film is doped and modified through a vapor infiltration cycle to prepare a PEI antistatic film based on precursor doping and modification.
[0039] Example 1 The present invention discloses a method for preparing a polyetherimide antistatic film based on precursor doping, comprising the following steps: ①Using deionized water, acetone and alcohol to ultrasonically clean the insulating glass sheet (1.5cm×1.5cm) several times, and then let it dry for later use; ② In the process of preparing the initial film, at room temperature, 0.1 g ml −1The NMP PEI solution was coated on a pre-cleaned glass sheet to prepare a polymer film with a thickness of 10 μm. The film was calcined at 80 °C for 12 h in a vacuum oven to remove excess solvent, and then the polymer film was heat treated in a vacuum oven at 200 °C for 1 h to complete thermal amination and obtain a PEI film; ③Finally, the prepared PEI initial film was placed in the reaction chamber of the ALD equipment, and the ZnO and H2O were subjected to gas phase infiltration cycles to achieve in-situ doping modification. The ZnO infiltration cycle included the following steps: the precursor vapor (DEZ) pulse entered the reaction chamber for 0.05s and remained in the reaction chamber for 75s, followed by a 75s N2 purge step to remove excess precursor molecules. Then, the H2O pulse entered the reaction chamber for 0.02s, the polymer matrix was exposed to the precursor for 75s, and finally purged with N2 for 75s. The deposition of DEZ and H2O was repeated 200 times to obtain a PEI / ZnO (200 cycles) film.
[0040] Example 2 The present invention discloses a method for preparing a polyetherimide antistatic film based on precursor doping, comprising the following steps: ①Using deionized water, acetone and alcohol to ultrasonically clean the insulating glass sheet (1.5cm×1.5cm) several times, and then let it dry for later use; ② In the process of preparing the initial film, at room temperature, 0.1 g ml −1 The NMP PEI solution was coated on a pre-cleaned glass sheet to prepare a polymer film with a thickness of 10 μm. The film was calcined at 80 °C for 12 h in a vacuum oven to remove excess solvent, and then the polymer film was heat treated in a vacuum oven at 200 °C for 1 h to complete thermal amination and obtain a PEI film; ③Finally, the prepared PEI initial film is placed in the reaction chamber of the ALD equipment, and TiO2, ZnO and H2O are used for gas phase infiltration cycle to achieve in-situ doping modification. The infiltration process of the precursor can be divided into two categories. Among them, a ZnO infiltration cycle includes the following steps: the precursor vapor (DEZ) pulse enters the reaction chamber for 0.05s and remains in the reaction chamber for 75s, and then a 75s N2 purge step is performed to remove excess precursor molecules. Then the H2O pulse enters the reaction chamber for 0.02s, the polymer matrix is exposed to the precursor for 75s, and finally purged with N2 for 75s. A TiO2 cycle includes the following steps: the precursor vapor (TiCl4) pulse enters the reaction chamber for 0.05s, the polymer matrix is exposed to the precursor for 75s, and finally purged with N2 for 75s to remove excess precursor molecules. Then, a H2O pulse of 0.02s entered the reaction chamber and remained in the reaction chamber for 75s, and finally N2 was purged for 75s to remove excess precursor molecules. The ratio we used was TiO2:ZnO=1:40, and the specific infiltration scheme was: first, the ZnO infiltration process was performed 50 times; then, a multi-precursor infiltration process was performed, that is, TiO2 infiltration was performed once, ZnO infiltration was performed 30 times, and this process was repeated 5 times. PEI / TZO (1:40) film was obtained.
[0041] During the permeation cycle of this embodiment, the temperature in the reaction chamber is 90° C. and the pressure is 10000-12000 Pa.
[0042] After the above three steps, a PEI / TZO (1:40) antistatic film based on multiple precursor doping modification was obtained.
[0043] Example 3 The present invention discloses a method for preparing a polyetherimide antistatic film based on precursor doping, comprising the following steps: ①Using deionized water, acetone and alcohol to ultrasonically clean the insulating glass sheet (1.5cm×1.5cm) several times, and then let it dry for later use; ② In the process of preparing the initial film, at room temperature, 0.1 g ml −1 The NMP PEI solution was coated on a pre-cleaned glass sheet to prepare a polymer film with a thickness of 10 μm. The film was calcined at 80 °C for 12 h in a vacuum oven to remove excess solvent, and then the polymer film was heat treated in a vacuum oven at 200 °C for 1 h to complete thermal amination and obtain a PEI film; ③Finally, the prepared PEI initial film is placed in the reaction chamber of the ALD equipment, and TiO2, ZnO and H2O are used for gas phase infiltration cycle to achieve in-situ doping modification. The infiltration process of the precursor can be divided into two categories. Among them, a ZnO infiltration cycle includes the following steps: the precursor vapor (DEZ) pulse enters the reaction chamber for 0.05s and remains in the reaction chamber for 75s, and then a 75s N2 purge step is performed to remove excess precursor molecules. Then the H2O pulse enters the reaction chamber for 0.02s, the polymer matrix is exposed to the precursor for 75s, and finally N2 is purged for 75s. A TiO2 cycle includes the following steps: the precursor vapor (TiCl4) pulse enters the reaction chamber for 0.02s, the polymer matrix is exposed to the precursor for 75s, and finally N2 is purged for 75s to remove excess precursor molecules. Then, a H2O pulse of 0.02s entered the reaction chamber and remained in the reaction chamber for 75s, and finally N2 was purged for 75s to remove excess precursor molecules. The ratio we used was TiO2:ZnO=2:40, and the specific infiltration scheme was: first, the ZnO infiltration process was performed 50 times; then, a multi-precursor infiltration process was performed, that is, TiO2 infiltration was performed 2 times, ZnO infiltration was performed 30 times, and this process was repeated 5 times. PEI / TZO (2:40) film was obtained.
[0044] During the permeation cycle of this embodiment, the temperature in the reaction chamber is 90°C and the pressure is 10000~12000Pa; After the above three steps, the PEI / TZO (2:40) antistatic film based on in-situ doping modification was obtained.
[0045] Example 4 The present invention discloses a method for preparing a polyetherimide antistatic film based on precursor doping, comprising the following steps: ①Using deionized water, acetone and alcohol to ultrasonically clean the insulating glass sheet (1.5cm×1.5cm) several times, and then let it dry for later use; ② In the process of preparing the initial film, at room temperature, 0.1 g ml −1 The NMP PEI solution was coated on a pre-cleaned glass sheet to prepare a polymer film with a thickness of 10 μm. The film was calcined at 80 °C for 12 h in a vacuum oven to remove excess solvent, and then the polymer film was heat treated in a vacuum oven at 200 °C for 1 h to complete thermal amination and obtain a PEI film; ③Finally, the prepared PEI initial film is placed in the reaction chamber of the ALD equipment, and TiO2, ZnO and H2O are used for gas phase infiltration cycle to achieve in-situ doping modification. The infiltration process of the precursor can be divided into two categories. Among them, a ZnO infiltration cycle includes the following steps: the precursor vapor (DEZ) pulse enters the reaction chamber for 0.08s and remains in the reaction chamber for 75s, and then a 75s N2 purge step is performed to remove excess precursor molecules. Then the H2O pulse enters the reaction chamber for 0.02s, the polymer matrix is exposed to the precursor for 75s, and finally N2 is purged for 75s. A TiO2 cycle includes the following steps: the precursor vapor (TiCl4) pulse enters the reaction chamber for 0.02s, the polymer matrix is exposed to the precursor for 75s, and finally N2 is purged for 75s to remove excess precursor molecules. Then, a H2O pulse of 0.02s entered the reaction chamber and remained in the reaction chamber for 75s, and finally N2 was purged for 75s to remove excess precursor molecules. The ratio we used was TiO2:ZnO=3:40, and the specific infiltration scheme was: first, the ZnO infiltration process was performed 50 times; then, a multi-precursor infiltration process was performed, that is, TiO2 infiltration 3 times, ZnO infiltration 30 times, and this process was repeated 5 times. PEI / TZO (3:40) film was obtained.
[0046] During the permeation cycle of this embodiment, the temperature in the reaction chamber is 90°C and the pressure is 10000~12000Pa; After the above three steps, the PEI / TZO (3:40) antistatic film based on in-situ doping modification was obtained.
[0047] Example 5 The present invention discloses a method for preparing a polyetherimide antistatic film based on precursor doping, comprising the following steps: ①Using deionized water, acetone and alcohol to ultrasonically clean the insulating glass sheet (1.5cm×1.5cm) several times, and then let it dry for later use; ② In the process of preparing the initial film, at room temperature, 0.1 g ml −1 The NMP PEI solution was coated on a pre-cleaned glass sheet to prepare a polymer film with a thickness of 10 μm. The film was calcined at 80 °C for 12 h in a vacuum oven to remove excess solvent, and then the polymer film was heat treated in a vacuum oven at 200 °C for 1 h to complete thermal amination and obtain a PEI film; ③Finally, the prepared PEI initial film is placed in the reaction chamber of the ALD equipment, and TiO2, ZnO and H2O are used for gas phase infiltration cycle to achieve in-situ doping modification. The infiltration process of the precursor can be divided into two categories. Among them, a ZnO infiltration cycle includes the following steps: the precursor vapor (DEZ) pulse enters the reaction chamber for 0.05s and remains in the reaction chamber for 75s, and then a 75s N2 purge step is performed to remove excess precursor molecules. Then the H2O pulse enters the reaction chamber for 0.02s, the polymer matrix is exposed to the precursor for 75s, and finally purged with N2 for 75s. A TiO2 cycle includes the following steps: the precursor vapor (TiCl4) pulse enters the reaction chamber for 0.05s, the polymer matrix is exposed to the precursor for 75s, and finally purged with N2 for 75s to remove excess precursor molecules. Then, a H2O pulse of 0.02s entered the reaction chamber and remained in the reaction chamber for 75s, and finally N2 was purged for 75s to remove excess precursor molecules. The ratio we used was TiO2:ZnO=4:40, and the specific infiltration scheme was: first, the ZnO infiltration process was performed 50 times; then, a multi-precursor infiltration process was performed, that is, TiO2 infiltration 4 times, ZnO infiltration 30 times, and this process was repeated 5 times. PEI / TZO (4:40) film was obtained.
[0048] During the permeation cycle of this embodiment, the temperature in the reaction chamber is 90°C and the pressure is 10000~12000Pa; After the above three steps, the PEI / TZO (4:40) antistatic film based on in-situ doping modification was obtained.
[0049] In the above examples, DEZ, TiCl4 and H2O were loaded into a chemical bottle in a glove box, and then a vapor permeation cycle was performed in the ALD equipment.
[0050] The present invention is further described in detail below in conjunction with the accompanying drawings: See also Figure 1, are SEM images of PEI / ZnO (200 cycles) and PEI / TZO (1:40) prepared by the scheme described in Example 1 and Example 2. In Figure a, very dense metal oxide nano-spherical particles appear, the main component of which is nano-ZnO particles, indicating the successful introduction of ZnO. As can be seen from Figure b, with the successful introduction of TiO2, cracking of the metal oxide layer appears on the surface of the film, which is the reason why titanium oxide may be phase separated in the zinc oxide film, but there are still quite dense oxide particles on its surface. The presence of the metal oxide layer on the surface of the film enables the surface of the film to dissipate static charges. The existence of the surface oxide layer can be explained by the fact that during the gas phase infiltration process, because the modification of the polymer matrix is carried out from top to bottom, and the gas phase infiltration process is a derivative of the atomic layer deposition process, it is inevitable that oxides will be deposited on the surface of the polymer matrix during the infiltration process.
[0051] See also Figure 2 , are O1s images of PEI / ZnO (200 cycles) and PEI / TZO (x:40) films after different VPI cycle treatments in Example 1, Example 2, Example 3, Example 4 and Example 5. With the increase of TiO2 doping ratio, it can be clearly seen that a new peak appears at 529~530eV, which is the characteristic peak of Ti-O bond, indicating that titanium oxide is successfully introduced into the polymer film. The characteristic peak of C=O shifts toward the direction of low binding energy with the increase of doping ratio. The main reason for this phenomenon is that the introduction of TiO2 intensifies the transformation of C=O to CO in PEI. At the same time, the characteristic peak of COC moves toward the high energy direction. Therefore, the XPS results show that the VPI process successfully introduces TiO2 particles into the PEI film and produces a strong doping effect on the polymer film.
[0052] See also Figure 3 , are IV curve images of PEI / ZnO (200 cycles) and PEI / TZO (x:40) films in Examples 1, 2, 3, 4 and 5. It can be seen intuitively that the electrical properties of the films doped with TiO2 are improved to varying degrees, and all show better electrical properties than those doped with ZnO alone, thus confirming the feasibility of the present invention to use vapor phase infiltration for in-situ doping and modification of the initial PEI film.
[0053] See also Figure 4, is a graph showing the change in conductivity of PEI / ZnO (200 cycles) and PEI / TZO (x:40) films after different VPI cycle treatments in Example 1, Example 2, Example 3, Example 4 and Example 5. Compared with doping with ZnO alone, the conductivity of TiO2-doped films has been improved to varying degrees, and the conductivity of PEI / TZO (1:40) is the best, specifically 3.56 S / cm. This data shows that the modified organic-inorganic hybrid film has excellent antistatic properties.
[0054] Figure 5 The friction voltage diagrams of PEI / ZnO (200 cycles) and PEI / TZO (x:40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention are shown. It can be seen that the friction voltage of PEI / TZO (1:40) is the smallest, indicating that the static charge on the surface of the film dissipates faster after modification, and the modified film has excellent antistatic properties.
[0055] Figure 6 The stress-strain curves of PEI / ZnO (200 cycles) and PEI / TZO (x:40) films after different VPI cycle treatments in Examples 1, 2, 3, 4 and 5 of the present invention are shown in FIG. As can be seen from the figure, the mechanical properties of some PEI / TZO samples after modification are improved compared with PEI (200 cycles).
[0056] In summary, this study adopts an effective way to modify the in-situ doping of PEI film based on vapor infiltration of atomic layer deposition, that is, in the embodiment, the precursor molecules are contacted with the polymer substrate, adsorbed into the polymer, diffused inside the polymer and reacted with the polymer chains inside the polymer. The introduction of the Ti element greatly enriches the number of metal oxide chains in the matrix, so the volume conductivity of the film is significantly improved. The metal oxide side chains act as charge discharge pathways inside the polymer, further accelerating the discharge rate of static charges. First of all, compared with the traditional methods of "surface modification" and "bulk doping", the doping process of the "vapor infiltration" method is controllable and the structure and properties of the modified polymer film are stable. Among them, the gas phase precursor molecules penetrate into the polymer matrix and react with the functional groups in its skeleton structure, that is, the introduced dopants can exist stably in the matrix, and no additional modification of the doping molecules is required.
[0057] In the above examples 1-5, the PEI film has abundant mesopores and micropores, which can effectively allow the gas phase precursor to enter the polymer and react. In view of the huge difference observed in the samples before and after permeation doping, it is more likely that the DEZ and TiCl4 precursor molecules interact with the functional groups of the polymer in some way, thereby facilitating electron conduction. Figure 2 It can be seen that when TiO2 is doped with PEI, the characteristic peak of the C=O double bond shifts, and an oxide peak is formed. This means that the Ti atom in the dopant molecule reacts with the oxygen-containing functional group in the matrix. TiCl4 can provide 4 binding sites, which will greatly increase the enrichment of metal oxides inside the polymer. At the same time, TiO2, as an impurity energy level, can serve as a center for the generation of electron-hole pairs. Under certain energy excitation, electrons on the impurity energy level are more likely to jump to the conduction band, while leaving holes in the valence band, thereby increasing the number of carriers, improving electrical properties, changing the electronic state, and providing a new transport path for the transport of carriers, thereby improving conductivity. The conductivity of the modified PEI film is 10 -6 -10 -4 S / cm, indicating that the material has excellent antistatic properties. Therefore, the method based on in-situ doping of polyetherimide antistatic film can be well applied to the application of polymer antistatic modification.
[0058] Example 6 A method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film comprises the following steps: 1) Place the PEI initial film into the reaction chamber of a vapor phase infiltration (VPI) device, control the pressure of the reaction chamber to 40 Pa, and then introduce inert gas at a flow rate of 40 sccm for 10 min; 2) ZnO permeation process, a ZnO cycle permeation process is: diethyl zinc vapor pulse 0.02s into the gas phase permeation chamber, and keep in the gas phase permeation chamber for 70s, and then N2 purge for 70s; then water vapor pulse 0.02s into the gas phase permeation chamber, and keep in the gas phase permeation chamber for 70s, and finally N2 purge for 70s, to complete a ZnO cycle permeation; 3) TiO2 infiltration process, a TiO2 cyclic infiltration process is as follows: a TiCl4 vapor pulse of 0.02s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 70s, and then N2 is purged for 70s; then a water vapor pulse of 0.02s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 70s, and finally N2 is purged for 70s to complete a TiO2 cyclic infiltration.
[0059] In addition, x is used to represent the number of infiltration cycles of TiO2, that is, the total number of infiltration cycles. The ratio of the total number of cycles of TiO2 to the total number of cycles of ZnO is 1:40, where the total number of cycles of ZnO is 200. First, ZnO is infiltrated, and step 2) is repeated 50 times to introduce the ZnO phase into PEI so that it reacts initially with the inside of the matrix. Then, multiple doping operations are performed, first TiO2 is infiltrated, step 3) is repeated once, followed by ZnO infiltration, step 2) is repeated 30 times, and the multiple doping operation is repeated 5 times to obtain a PEI / TZO (1:40) film.
[0060] During the permeation cycle, the temperature in the reaction chamber is 90° C. and the pressure is 10000 Pa.
[0061] The conductivity of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film prepared in this embodiment is 1.1×10 -5 S / cm, the friction voltage is -0.25V, and the stress is 10.2Mpa.
[0062] Example 7 A method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film comprises the following steps: 1) Place the PEI initial film into the reaction chamber of the vapor phase infiltration (VPI) device, control the pressure of the reaction chamber to 50 Pa, and then introduce inert gas at a flow rate of 60 sccm for 10 min; 2) ZnO permeation process, a ZnO cyclic permeation process is: diethyl zinc vapor pulse 0.03s into the gas phase permeation chamber, and keep it in the gas phase permeation chamber for 72s, and then N2 purge for 72s; then water vapor pulse 0.03s into the gas phase permeation chamber, and keep it in the gas phase permeation chamber for 72s, and finally N2 purge for 72s, completing a ZnO cyclic permeation; 3) TiO2 infiltration process, a TiO2 cyclic infiltration process is as follows: a TiCl4 vapor pulse of 0.03s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 72s, and then N2 is purged for 72s; then a water vapor pulse of 0.03s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 72s, and finally N2 is purged for 72s to complete a TiO2 cyclic infiltration.
[0063] In addition, x is used to represent the number of infiltration cycles of TiO2, that is, the total number of infiltration cycles. The ratio of the total number of cyclic infiltration cycles of TiO2 to the total number of infiltration cycles of ZnO is 2:40, where the total number of cycles of ZnO is 200. First, ZnO is infiltrated, and step 2) is repeated 50 times to introduce the ZnO phase into PEI so that it reacts initially with the inside of the matrix. Then, multiple doping operations are performed, first TiO2 is infiltrated, and step 3) is repeated 2 times, followed by ZnO infiltration, and step 2) is repeated 30 times. The multiple doping operation is repeated 5 times to obtain a PEI / TZO (2:40) film.
[0064] During the permeation cycle, the temperature in the reaction chamber is 92° C. and the pressure is 11000 Pa.
[0065] The conductivity of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film prepared in this embodiment is 2×10 -5 S / cm, the friction voltage is 0.1V, and the stress is 10.5Mpa.
[0066] Example 8 A method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film comprises the following steps: 1) Place the PEI initial film into the reaction chamber of the vapor phase infiltration (VPI) device, control the pressure of the reaction chamber to 75 Pa, and then introduce inert gas at a flow rate of 75 sccm for 10 min; 2) ZnO infiltration process, a ZnO cyclic infiltration process is: diethyl zinc vapor pulse 0.05s into the gas phase infiltration chamber, and keep it in the gas phase infiltration chamber for 75s, and then N2 purge for 75s; then water vapor pulse 0.05s into the gas phase infiltration chamber, and keep it in the gas phase infiltration chamber for 75s, and finally N2 purge for 75s, to complete a ZnO cyclic infiltration; 3) TiO2 infiltration process, a TiO2 cyclic infiltration process is as follows: a TiCl4 vapor pulse of 0.05s enters the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 75s, and then N2 is purged for 75s; then a water vapor pulse of 0.05s enters the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 75s, and finally N2 is purged for 75s to complete a TiO2 cyclic infiltration.
[0067] The ratio of the total number of cycles of TiO2 infiltration to the total number of cycles of ZnO infiltration is 4:40, of which the total number of cycles of ZnO is 200. First, ZnO is infiltrated, and step 2) is repeated 50 times to introduce the ZnO phase into PEI so that it reacts initially with the inside of the matrix. Then, multiple doping operations are performed, first TiO2 is infiltrated, and step 3) is repeated 4 times, followed by infiltration of ZnO, and step 2) is repeated 30 times. The multiple doping operation is repeated 5 times to obtain a PEI / TZO (4:40) film.
[0068] During the permeation cycle, the temperature in the reaction chamber is 95° C. and the pressure is 12000 Pa.
[0069] The conductivity of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film prepared in this embodiment is 3.6×10 -5 S / cm, the friction voltage is 0.8V, and the stress is 10.6Mpa.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film, characterized in that: The following steps are involved: The titanium oxide / zinc oxide co-doped polyetherimide antistatic film is prepared by sequentially and cyclically permeating ZnO and TiO2 on the PEI film several times by using a vapor phase permeation method; Among them, the ratio of the total number of cyclic penetrations of TiO2 to the total number of cyclic penetrations of ZnO is (1~4):
40.
2. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to claim 1, characterized in that: The total number of infiltration cycles of ZnO is 200 times, and the total number of infiltration cycles of TiO2 is 5~20 times.
3. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to claim 1, characterized in that: The ZnO and TiO2 were infiltrated on the PEI film in turn by gas phase infiltration method for several times, specifically: First, 50 ZnO infiltration cycles were performed, and then TiO2 infiltration cycles and ZnO infiltration cycles were performed alternately for a total of 5 times. In each alternating infiltration, TiO2 infiltration cycles were performed 1 to 4 times, and ZnO infiltration cycles were performed 30 times.
4. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to claim 1, characterized in that: The vapor phase infiltration method was used to cyclically infiltrate ZnO and TiO2 on the PEI film for several times. Specifically, 50 ZnO infiltration cycles were performed first, and then TiO2 infiltration cycles and ZnO infiltration cycles were performed alternately for a total of 5 times. In each alternating infiltration, TiO2 infiltration cycle was performed once and ZnO infiltration cycle was performed 30 times.
5. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to any one of claims 1 to 4, characterized in that: A ZnO cycle permeation process is as follows: a pulse of diethyl zinc vapor is introduced into a gas phase permeation chamber for 0.02 to 0.05 seconds, and the chamber is kept in the gas phase permeation chamber for 70 to 75 seconds, and then N2 is purged for 70 to 75 seconds; a pulse of water vapor is introduced into the gas phase permeation chamber for 0.02 to 0.05 seconds, and the chamber is kept in the gas phase permeation chamber for 70 to 75 seconds, and finally N2 is purged for 70 to 75 seconds, thereby completing a ZnO cycle permeation; One of the TiO2 cyclic infiltration processes is as follows: a TiCl4 vapor pulse of 0.02 to 0.05 s is introduced into the gas phase infiltration chamber, and maintained in the gas phase infiltration chamber for 70 to 75 s, and then N2 is purged for 70 to 75 s; then a water vapor pulse of 0.02 to 0.05 s is introduced into the gas phase infiltration chamber, and maintained in the gas phase infiltration chamber for 70 to 75 s, and finally N2 is purged for 70 to 75 s to complete a TiO2 cyclic infiltration.
6. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to any one of claim 5, characterized in that: A ZnO cycle permeation process is as follows: a pulse of diethyl zinc vapor is introduced into the gas phase permeation chamber for 0.05 s, and the chamber is kept in the gas phase permeation chamber for 75 s, and then N2 is purged for 75 s; a pulse of water vapor is introduced into the gas phase permeation chamber for 0.02 s, and the chamber is kept in the gas phase permeation chamber for 75 s, and finally N2 is purged for 75 s, to complete a ZnO cycle permeation; One of the TiO2 cyclic infiltration processes is as follows: a TiCl4 vapor pulse of 0.05s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 75s, and then N2 is purged for 75s; then a water vapor pulse of 0.02s is introduced into the gas phase infiltration chamber, and is maintained in the gas phase infiltration chamber for 75s, and finally N2 is purged for 75s to complete a TiO2 cyclic infiltration.
7. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to claim 6, characterized in that: During the ZnO cyclic infiltration process and the TiO2 cyclic infiltration process, the temperature of the gas phase infiltration chamber is maintained at 90-95°C and the pressure is maintained at 10000-12000Pa.
8. The method for preparing a titanium oxide / zinc oxide co-doped polyetherimide antistatic film according to claim 1, characterized in that: Before cyclically infiltrating ZnO and TiO2 on the PEI film in sequence by vapor infiltration, the PEI film is placed in a vapor infiltration chamber, and the pressure in the vapor infiltration chamber is controlled to be 40-75 Pa, and then an inert gas is introduced at a flow rate of 40-75 sccm for 10 minutes.
9. A titanium oxide / zinc oxide co-doped polyetherimide antistatic film, characterized in that: The titanium oxide / zinc oxide co-doped polyetherimide antistatic film is prepared by the method described in any one of claims 1 to 8; the conductivity of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film is (1.1~3.6)×10 -5 S / cm, the friction voltage is -0.25~0.8V, and the stress is 10.2~10.6Mpa.
10. Use of the titanium oxide / zinc oxide co-doped polyetherimide antistatic film as claimed in claim 9 in antistatic equipment.
Citation Information
Patent Citations
Preparation method of zinc oxide doped titanium oxide film for photocatalysis
CN103361631A
Titanium-ion-containing co-doped zinc oxide light-emitting film and preparation method and application thereof
CN103571460A
Alumina / zinc oxide co-doped polythiophene derivative conductive film and preparation method and application thereof
CN116640350A
Method for producing organic-inorganic hybrid materials
US20210292899A1